2021
DOI: 10.3389/fpsyt.2021.610457
|View full text |Cite
|
Sign up to set email alerts
|

Digital Communication Biomarkers of Mood and Diagnosis in Borderline Personality Disorder, Bipolar Disorder, and Healthy Control Populations

Abstract: Background: Remote monitoring and digital phenotyping harbor potential to aid clinical diagnosis, predict episode course and recognize early signs of mental health crises. Digital communication metrics, such as phone call and short message service (SMS) use may represent novel biomarkers of mood and diagnosis in Bipolar Disorder (BD) and Borderline Personality Disorder (BPD).Materials and Methods: BD (n = 17), BPD (n = 17) and Healthy Control (HC, n = 21) participants used a smartphone application which monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…Gillett et al ( 9 ) showed a significant interaction between a bipolar disorder population and smartphone use. A negative correlation is highlighted between total outgoing call frequency, total duration, total outgoing SMS messaging frequency and bipolar depressive episodes.…”
Section: Resultsmentioning
confidence: 99%
“…Gillett et al ( 9 ) showed a significant interaction between a bipolar disorder population and smartphone use. A negative correlation is highlighted between total outgoing call frequency, total duration, total outgoing SMS messaging frequency and bipolar depressive episodes.…”
Section: Resultsmentioning
confidence: 99%
“…Large, multilevel data sets will enable deep phenotyping and distinguish pathophysiological pathways (Phillips & Kendler, 2021 ). For example, remote monitoring can complement symptom monitoring and capture signals more representative of the underlying pathophysiology of BD and BPD (Gillett et al, 2021 ; Gillett & Saunders, 2019 ). One of the ways to conduct remote monitoring is Experience Sampling Methodology (ESM).…”
Section: Discussionmentioning
confidence: 99%